1993
DOI: 10.1007/bf00006198
|View full text |Cite
|
Sign up to set email alerts
|

The functioning of the ecosystem of the Banc d'Arguin, Mauritania: a review

Abstract: The Banc d'Arguin, Mauritania, is an area of over 10000 km 2 of shallow water and tidal flats between the Sahara and the upwelling system off the Mauritanian coast . The results of the Dutch-Mauritanian project `Banc d'Arguin 1988' as well as the relevant literature are reviewed in order to develop a preliminary conceptual model of the functioning of this ecosystem . Hydrographically the Banc d'Arguin can be characterized as a large-scale negative estuary with higher salinities near the shore . It is concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…The benthic macrofauna of this area is actively exploited by shorebirds and motile marine predators (Wolff et al, 1993b(Wolff et al, , 2005Ahmedou Salem et al, 2014). Because of this, approximately 12,000 km 2 of shallow water, tidal flats, and adjacent desert have been included in a marine protected area called the Parc National du Banc d'Arguin (PNBA) since 1976.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The benthic macrofauna of this area is actively exploited by shorebirds and motile marine predators (Wolff et al, 1993b(Wolff et al, , 2005Ahmedou Salem et al, 2014). Because of this, approximately 12,000 km 2 of shallow water, tidal flats, and adjacent desert have been included in a marine protected area called the Parc National du Banc d'Arguin (PNBA) since 1976.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, apart from an exploration of ecological interactions between the entire BA and the upwelling input (Wolff et al, 1993b), the subtidal food web structure of the gulf is poorly known, mainly because scientific cruises to this area have been hampered by its extreme shallowness and poorly described bottom topography. In addition, the high carrying capacity of the BA tidal flat area for wintering shorebirds is still not fully understood (Wolff et al, 1993a;van der Geest, 2013;Ahmedou Salem et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the genetic structure of the Cymodocea nodosa meadows in Ria Formosa suggested that this population was likely introduced from a single male ''founder'' clone (Alberto et al 2001), which may be derived from either the northern Africa or the Mediterranean meadows. A further peculiarity of Ria Formosa as a habitat for Cymodocea nodosa is that it is a highly productive, nutrient-rich system wnitrate concentrations up to 8.8 mM, phosphates up to 5.6 mM and ammonium concentrations up to 108 mM (Falcã o and Vale 1990)x, whereas all other Atlantic meadows investigated grow in oligotrophic or mesotrophic environments (Wolff et al 1993, Pé rez et al 1994. The growth of Cymodocea nodosa is often nutrient-limited (Pé rez et al 1994), so growth and production in Ria Formosa may be particularly high.…”
Section: Introductionmentioning
confidence: 99%